Penguatan Identitas Bangsa melalui Pendidikan Multikultural Tinjauan Lanjutan dari Galatia 5:22-23: Menurut Prespektif Sosiologi - Lubis, Menti Riani (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
Indonesia, a country rich in social, ethnic, linguistic and religious diversity, has upheld solidarity in diversity since independence in 1945. The motto